2017
DOI: 10.1055/s-0043-103409
|View full text |Cite
|
Sign up to set email alerts
|

Extending magnifying NBI diagnosis of intestinal metaplasia in the stomach: the white opaque substance marker

Abstract: Intestinal metaplasia (IM) of the stomach is associated with an increased risk of differentiated gastric cancer. While it is important to diagnose IM endoscopically, it can be difficult to observe by white-light endoscopy. In magnifying endoscopy with narrow-band imaging (M-NBI) of the stomach, a light-blue crest (LBC) is widely known to be a useful marker in the endoscopic diagnosis of IM. However, IM that exhibits only white opaque substance (WOS) without an LBC can also occur. The aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 18 publications
(11 reference statements)
2
48
0
1
Order By: Relevance
“…Our data showed that LCS using LCI had slightly higher diagnostic accuracy for GIM than that shown in a recent report for NBI [10]. LCI enables the detection of not only bluish-whitish patchy areas in NBI as LCS but also GIM as mottled patchy erythema and map-like redness, which typically appear after H. pylori eradication in patients with severe atrophy [25,26].…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Our data showed that LCS using LCI had slightly higher diagnostic accuracy for GIM than that shown in a recent report for NBI [10]. LCI enables the detection of not only bluish-whitish patchy areas in NBI as LCS but also GIM as mottled patchy erythema and map-like redness, which typically appear after H. pylori eradication in patients with severe atrophy [25,26].…”
Section: Discussionsupporting
confidence: 43%
“…Uedo et al [8] reported that the sensitivity and specificity of LBC as a predictor of GIM were 89 and 93%, respectively, and Kanemitsu et al [10] reported that those of white opaque substance were 50 and 100% respectively. Although GIM is observed as bluish-whitish patchy areas in the antrum using NBI without magnification, a meta-analysis of the diagnosis of GIM using NBI without magnification showed that the sensitivity and specificity were 0.69 and 0.91 respectively [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, dysplasia or cancer may present as a “white opaque substance,” which, as the name implies, is characterized by white material above the mucosa [10, 31, 33, 34]. However, a white opaque substance has also been associated with intestinal metaplasia, so it is not a specific marker [39]. …”
Section: Stomachmentioning
confidence: 99%
“…ME-NBI has also been proven useful in the diagnosis of early gastric cancer, and the Magnifying Endoscopy Simple Diagnostic Algorithm for Early Gastric Cancer (MESDA-G) was recommended for the evaluation of a suspicious gastric lesion [39]. It applies the Vessels plus Surface Classification and suggests evaluation with NBI if a clear border between the suspicious lesion and the background mucosa (demarcation line) exists: if absent, it excludes cancer; if present, microvascular and microsurface patterns should be evaluated.…”
Section: Stomachmentioning
confidence: 99%